Blocking the A2B adenosine receptor alleviates myocardial damage by inhibiting spleen-derived MDSC mobilisation after acute myocardial infarction. (31st December 2022) - Yu, Zongying; Ling, Yang; Xu, Qiancheng; Cao, Yuhan; Tang, Shengxing; Fu, Cong
Abstract: Background: Myeloid-derived suppressor cell (MDSC) mobilisation is an important immune event in acute myocardial infarction (AMI). The A2B adenosine receptor (A2B AR) plays key role in regulating MDSC function, but its specific involvement in MDSC mobilisation in AMI remains unclear. Methods: In AMI patients, the circulating MDSC ratio and A2B AR mRNA expression were measured. A mouse AMI model was established by left anterior descending coronary artery (LADCA) ligation. MDSCs were analysed by FACS and immunofluorescence staining (of heart tissue). A2B AR mRNA expression was assessed by qRT-PCR. Myocardial injury was detected by HE staining. Myocardial cell apoptosis was analysed by immunohistochemistry. Cardiac systolic function was evaluated by transthoracic echocardiography. Results: In AMI patients, the circulating MDSC ratio was increased and positively correlated with A2B AR mRNA expression ( r = 0.86, p < 0.01). In AMI model mice, the percentage of MDSCs was increased in the circulation and infarcted heart and decreased in the spleen. MRS-1754-mediated A2B AR inhibition decreased the MDSC ratio in the circulation and infarcted heart and prevented the decrease in MDSC number in the spleens of mice with AMI. A2B AR blockade inhibited myocardial cell apoptosis, alleviated myocardial inflammatory injury, and improved myocardial systolic function in the AMI mouse model. Similar results were found in mice after splenectomy. Additionally, spleen-derived MDSC injection increased the MDSC ratio in the infarcted heart, increased myocardial cell apoptosis, aggravated myocardial injury, and decreased cardiac systolic function in mice with AMI. Conclusion: Blocking A2B AR alleviates myocardial damage and improves myocardial systolic function through inhibition of spleen-derived MDSC mobilisation after AMI. Key Messages: Spleen-derived MDSC mobilisation aggravates myocardial inflammatory injury within 24 h of AMI. A2B AR promotes spleen-derived MDSC mobilisation within 24 h of AMI. Blocking A2B AR improves myocardial systolic function through inhibition of spleen-derived MDSC mobilisation.